STRATEGI PEMERINTAH DAERAH DALAM UPAYA PENGUATAN ECOLOGICAL CITIZENSHIP PADA PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KABUPATEN SUKOHARJO - Nugroho, Dedy Ari; ., Suharno (PKn Progresif, 2017)
ABSTRACTThis study examined community-based citizenship knowledge about the strategy of Local Government in an effort to strengthen ecological citizenship in City Without Slum Program (KOTAKU). The content of this research was presented theoretically based on the data of descriptive qualitative research and supported by literature study conducted in Sukoharjo District, Central Java Province. The ecological development program used as the object of research was the City Without Slum Program (KOTAKU). Scientific work of this research was made as a reflection on the issue of citizenship, especially about the problem of apathism in society in various development activities in the field of environmental control. As a country of democracy, Indonesia proves itself that the state has been concerned with the participation of its people. Community participation in the field of environmental development can be done through the Program of City Without Slum (KOTAKU), which is held in all parts of Indonesia including in Sukoharjo District. Community education conducted by the Local Government is one of the strategic efforts, that can be done to strengthen itself as a democratic government and care about the accessibility of the community to participate in the field of environmental (ecological) development. While the focus of this study was related to the efforts of Local Government and the community in the program of healthy environmental control, which is the field of study of Pancasila and Citizenship Education, and termed as ecological citizenship.Keywords: City Without Slum Program (KOTAKU), civics, ecological citizenship, Local Government, Participation